(untitled) (Anclajes, 2022)
The publishing company founded in Paris by Uruguayan brothers Alfredo and Armando Guido edited a series of magazines aimed at the Spanish-speaking public of Latin America. Between 1911 and 1914, literary editor Rubén Darío sent contributions to two of them, Elegancias and Mundial Magazine. The former, sought female readership on both sides of the Atlantic, was an abundantly illustrated magazine while Elegancias also lent a modest importance to photography. We analyze this topic from an article that appeared in issue number 42, “El arte y la fotografia”, in which the scope of this technical medium is discussed.